2003
DOI: 10.1106/002199803028676
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Analysis of Pulling Force in Pultrusion and Resin Injection Pultrusion (RIP)–Part I: Experimental

Abstract: Pulling force is the summation of resistance forces along a pultrusion die. Its mechanism is complicated because the impregnated resin inside the compressed fiber reinforcement changes from a liquid to a gel, and finally to a solid in the die. Two methods, a ‘mat tracer’method and a ‘short die length’ method, were used to determine the pulling force distribution. Results show that the downstream part of the die contributes little to the pulling force. In order to predict the resistance force in both the injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…Jeswani et al (2009) also revealed that the increase of pulling speed improved the properties of the pultruded profile. Li et al (2003) implemented mat tracer method and short die length method in studying the effect of die length on the pulling speed in pultrusion process. The increase of the die length does not affect the pulling force.…”
Section: Processing Parametersmentioning
confidence: 99%
“…Jeswani et al (2009) also revealed that the increase of pulling speed improved the properties of the pultruded profile. Li et al (2003) implemented mat tracer method and short die length method in studying the effect of die length on the pulling speed in pultrusion process. The increase of the die length does not affect the pulling force.…”
Section: Processing Parametersmentioning
confidence: 99%
“…Pull Force Model. As aforementioned, four different contributions to the overall pulling force in pultrusion have been identified in the literature [2,3,[14][15][16][17][18][19][20][21]: the collimation force col , the bulk compaction force bulk , the viscous drag vis , and the frictional force fric . These contributions are strictly related to the geometrical features of the die-work piece system and to the resin transitions from liquid to gel and then solid status, as schematized in Figure 3.…”
Section: Theoretical Modeling and Numerical Implementationmentioning
confidence: 99%
“…It should be noted that the value of the friction coefficient depends on the DOC during the resin gelation and further varies at the glass transition. However, due to the lack of thorough experimental data, generally the averaged values are utilized [14][15][16][17][18][19][20][21]. Regarding the magnitude of the contact pressure, is considered to be affected by two contrasting conditions: the transverse thermal expansion of the composite due to the increase in temperature and pressure and the resin chemical shrinkage related to crosslinking reaction.…”
Section: Theoretical Modeling and Numerical Implementationmentioning
confidence: 99%
See 2 more Smart Citations